Do cuidado: da essência da existência do ser-aí em Heidegger. - Weyh, Katyana Martins (2019)
The present dissertation intends to investigate the theme of care (Sorge) in the scope of the existential analytic (philosophical project intrinsic to the book Being and time), of the German philosopher Martin Heidegger (1889-1976). From this theme, we can formulate the problem: how does care - as the existential structure of being-there (Dasein) - constitute, according to Heidegger, the essence of existence? In view of this thematic question, we assume by main objective to determine, from the existential analytic, how existential care constitutes the essence of the existence of being-there and how it appears as the structural totality of the being of being-there. For this objective to be achieved, the work will deal with themes that are intrinsic to existential analytics, such as the rehabilitation of the ontological-fundamental question (the question about the meaning of being), the deconstruction of the history of ontology and the hermeneutic phenomenology of facticity.It is indispensable to go through these themes to understand the fundamental project of Being and time, namely: the fundamental ontology, which embrace all the other projects that constitute it.It is in the project of existential analytics that Heidegger presents the notion of being-there (Dasein) as the only ontological-ontological entity capable of embrace being and its meaning. In the quest for the characterization of being-there, and to understand more deeply its way of being, we describe its existential constitution in view of its essentially embracing, mundane and decadent character. The theme of care emerges, therefore, among these themes, described more punctually after the crisis of anxiety, understood as a fundamental affective tone. Given this, we have the hypothesis that care is the ontological-existential way of being-there. In this way, it will be possible to show how care is articulated with some of the fundamental concepts of Heidegger's phenomenology, such as the fundamental affective tonality of anxiety, decision, existential project, the voice of consciousness and the notion of being-for-a-death.